Health saving technologies in the training of future primary school teachers - N.D. Karapuzova (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose : To reveal the features of the application of technology in the health-professional training of future primary school teachers and to characterize their practical implementation. Material : The study involved 137 students. Test was used to determine the likelihood of stress on G. Nemchin and J. Taylor. Results : It was found that the vast majority of respondents (67%) have a low level of efficiency and high stress. That is, there is the possibility of negative effects of stress. Among the students of middle and low level of success of 76% the cause of this was called exhaustion. Defined as the implementation of technologies will aggregate pedagogically appropriate forms, methods and means of organization and management of the educational process. Proposed criteria indicators of training activities from the standpoint of health preservation. An experience of work on the implementation of health-technology in the practice of psycho-pedagogical faculty. Conclusions : The health-tech feature is the harmonious combination of training, educational and developing pedagogical influences. They are specified in the learning and cognitive, research, organizational and educational work of the students and the teaching practice in schools. They are aimed at both the development and improvement of the physical, spiritual, mental and social health factors of a young man, and on the formation of health-competence of students.